Voice and Swallowing Disorders - Ahmed, Monjur (IntechOpen, 2020)
The purpose of writing this book is to discuss the updated information on voice and swallowing disorders. The book has been written by international authors and experts in this field. You will find not only clinical aspects but also basic science aspects of voice and swallowing disorders. The chapters include the quantitative analysis of activity patterns of muscles of mastication and deglutition, and salivary secretion after facial massage and vibrotactile stimulation. You will also find the updated management of oropharyngeal dysphagia, dysphagia due to cervical facial tumors, radiation-induced dysphagia, and dysphagia in patients with a stroke. This book can be an important guide to the practicing physicians and surgeons managing voice and swallowing disorders.